Analisis Aktivitas dan Rentabilitas terhadap Efektifitas Kinerja Keuangan - Rahmat Kurnia; Febi Rahmat; Riandy Mardhika Adif (SAFE-Network, 2023)
This study aims to determine the effectiveness of the company's financial performance PT. Light Metal Industry Alumindo Tbk. The problem in this research is the net profit of PT. Alumindo Light Metal Industry Tbk has suffered losses in a row, namely in 2019-2021. The purpose of this research is to analyze PT. Alumindo Light Metal Industry Tbk as seen from the activity ratio and profitability ratio. This type of research is field research, with the research method used is descriptive quantitative. This research was conducted at PT. Alumindo Light Metal Industry Tbk accessed through the official website of the Indonesian stock exchange, namely www.idx.co.id. The data collection technique in this study is a documentation technique in the form of financial reports. Research conducted at PT. Alumindo Light Metal Industry Tbk, which the author accesses through the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The data collection technique in this study is a collection technique in the form of financial statements of PT. Light Metal Industry Alumindo Tbk. PT. Light Metal Industry Alumindo Tbk. The results showed that the financial performance of PT. Alumindo Light Metal Industry Tbk for the last five years starting in 2018-2022 when viewed from the activity ratio it shows financial performance that has not been effective. Meanwhile, when viewed from the profitability ratios, the company's performance is in a bad condition.